The Triumph and the Threshold: Ciriaco d’Ancona and the Renaissance Discovery of the Ancient Arch - Gudelj, Jasenka (Array, 2014)
The article delineates the approach of the antiquarian Ciriaco d'Ancona to antique arches and city gates in Italy, Greece and the East Adriatic coast, defining him the major connoisseur of this building type in the first half of the fifteenth century. It also defines Ciriaco's Dubrovnik visits as seminal for the emulation of the ancient practice of erecting arches.